A passion for leadership ebook Lessons on change and reform from fifty years of public service. - Gates, Robert M. (2016)
From the former secretary of defense and author of the acclaimed #1 best-selling memoir  Duty, a characteristically direct, informed, and urgent assessment of why big institutions are failing us and how smart, committed leadership can effect real improvement regardless of scale. Across the realms of civic and private enterprise alike, bureaucracies vitally impact our security, freedoms, and everyday life. With so much at stake, competence, efficiency, and fiscal prudence are essential, yet Americans know these institutions fall short. Many despair that they are too big and too hard to reform. Robert Gates disagrees. Having led change successfully at three monumental organizations—the CIA, Texas A&M University, and the Department of Defense—he offers us the ultimate insider’s look at how major bureaus, organizations, and companies can be transformed, which is by turns heartening and inspiring and always instructive. With practical, nuanced advice on tailoring reform to the operative culture (we see how Gates worked within the system to increase diversity at Texas A&M); effecting change within committees; engaging the power of compromise (“In the real world of bureaucratic institutions, you almost never get all you want when you want it”); and listening and responding to your team, Gates brings the full weight of his wisdom, candor, and devotion to civic duty to inspire others to lead desperately needed change.